Implementasi Mekanisme Carry and Forward Antar Broker MQTT pada Lingkungan dengan Konektivitas Tidak Stabil (Intermittent Connection) - Dyah Ayu Ocky Mawardani; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Connecting internal system of IoT through internet can be done using MQTT protocol. MQTT was designed for application that required data collection accross constrained networks. However, its architecture doesn't support to handle mobility if the disconnected period takes longer time. It also has not been able to handle the problem of data delivery in intermittent connectivity environment. As a solution to handle such problem, this research focused on implementation carry and forward mechanism between MQTT brokers. The tests that were carried out include functionality, success rate, and delay between nodes. In functionality test, the functional requirements that have been designed, can be met by server and client. In success rate test, the results show the success rate of data delivery is 100%. The average delay between nodes from publisher 1 to local broker 32.63 seconds, local broker to broker agent 33.01 seconds and broker agent to subscribers 1, 2, and 3 respectively, 603181.91 seconds, 603201.15 seconds, and 603193.48 seconds. Then, from publisher 2 to local broker 78.31 seconds, local broker to broker agent 30.90 seconds and broker agent to subscriber 1, 2, and 3 respectively, 2118.80 seconds, 2110.62 seconds, and 2112.32 seconds. Last, from publisher 3 to local broker 78.55 seconds, local broker to agent broker 30.90 seconds and agent broker to subscribers 1, 2 and 3, respectively, 605302.96 seconds, 605313.72 seconds, and 605322.29 seconds.